A quantitative genome-wide RNAi screen in C. elegans for antifungal innate immunity genes. Issue 1 (December 2016) - Zugasti, Olivier; Thakur, Nishant; Belougne, Jérôme; Squiban, Barbara; Kurz, C.; Soulé, Julien; Omi, Shizue; Tichit, Laurent; Pujol, Nathalie; Ewbank, Jonathan
Abstract Background Caenorhabditis elegans has emerged over the last decade as a useful model for the study of innate immunity. Its infection with the pathogenic fungusDrechmeria coniospora leads to the rapid up-regulation in the epidermis of genes encoding antimicrobial peptides. The molecular basis of antimicrobial peptide gene regulation has been previously characterized through forward genetic screens. Reverse genetics, based on RNAi, provide a complementary approach to dissect the worm's immune defenses. Results We report here the full results of a quantitative whole-genome RNAi screen inC. elegans for genes involved in regulating antimicrobial peptide gene expression. The results will be a valuable resource for those contemplating similar RNAi-based screens and also reveal the limitations of such an approach. We present several strategies, including a comprehensive class clustering method, to overcome these limitations and which allowed us to characterize the different steps of the interaction betweenC. elegans and the fungusD. coniospora, leading to a complete description of the MAPK pathway central to innate immunity inC. elegans . The results further revealed a cross-tissue signaling, triggered by mitochondrial dysfunction in the intestine, that suppresses antimicrobial peptide gene expression in the nematode epidermis. Conclusions Overall, our results provide an unprecedented system's level insight into the regulation ofC. elegans innate immunity. They represent a significant contribution to our understanding of host defenses and will lead to a better comprehension of the function and evolution of animal innate immunity.